KAJIAN TEKNIS PRODUKSI ALAT MUAT DAN ALAT ANGKUT PADA KEGIATAN PENAMBANGAN BATUBARA - muhammad dafa ramadhan (PERHAPI, 2023)
This research aims to calculate the production capability of loading and conveyance equipment used in coal mining activities, find out what factors affect the non-achievement of coal production suggestions, and then make efforts to increase the production of loading and conveyance equipment so that the targets that have been set can be achieved. . In this study, observation and retrieval of data in the field directly (primary data) and indirectly (secondary data) will then be carried out data processing. Based on the results of calculations, it can be concluded that the production of Komatsu PC400LC Excavator loading equipment is 18,651.11 Tons / month and the production of 4 units of Nissan CWB450HD Dump Truck conveyance is 18.325,66 Tons / month. Factors that cause non-achievement of production targets on loading equipment and conveyance are low work efficiency due to loss of working time and non-optimal distribution time due to road conditions that do not meet the standards. Efforts to increase the production of load tools were made by increasing work efficiency from 63.56% to 64.32%, so that the production target increased to 20,761.54 tons / month. For conveyance, the first alternative that can be done to increase production is to increase work efficiency from 63.34% to 64.10% and optimize the distribution time of conveyance from 359.77 seconds to 330.10 seconds, so that production increases to 20.212,45 Tons / month. The second alternative that can be done is to increase the work efficiency and increase the number of bucket fillings from 3 times to 4 times, so that production increases to 21.986,50 Tons / month.